2015
DOI: 10.1002/rcm.7306
|View full text |Cite
|
Sign up to set email alerts
|

Traceability of different apple varieties by multivariate analysis of isotope ratio mass spectrometry data

Abstract: This study proves the potential of stable isotopes to discriminate the geographical origin of apples grown in orchards located only a few hundreds of kilometres apart. Stable isotopes were also able to discriminate different apple varieties, although only within small geographical areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
(36 reference statements)
3
11
1
1
Order By: Relevance
“…The fingerprinting methods based on mineral element composition of food stuff have been largely adopted in the last years to trace the geographical origin of wine, olive oil, honey, cheese, coffee, vegetable, fruits, and spices (Danezis et al, 2016). One of the most popular techniques adopted for these analyses is the inductively-coupled plasma mass spectrometry (ICP-MS), which can be used for the determination of both the ionomic profile and the isotope ratios (Baxter et al, 1997; Rebolo et al, 2000; Wieser et al, 2001; Castiñeira et al, 2004; Coetzee et al, 2005; Šelih et al, 2014; Capici et al, 2015; Mimmo et al, 2015; Popescu et al, 2015; Scampicchio et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The fingerprinting methods based on mineral element composition of food stuff have been largely adopted in the last years to trace the geographical origin of wine, olive oil, honey, cheese, coffee, vegetable, fruits, and spices (Danezis et al, 2016). One of the most popular techniques adopted for these analyses is the inductively-coupled plasma mass spectrometry (ICP-MS), which can be used for the determination of both the ionomic profile and the isotope ratios (Baxter et al, 1997; Rebolo et al, 2000; Wieser et al, 2001; Castiñeira et al, 2004; Coetzee et al, 2005; Šelih et al, 2014; Capici et al, 2015; Mimmo et al, 2015; Popescu et al, 2015; Scampicchio et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In our study, δ 15 N values ranged from -0.5 to 9.2 ‰ with a mean value of 2.4 ‰, which is lower than the soil δ 15 N value. Mimmo et al [25] observed similar values, ranging between 1.1 and 3.0 ‰. We could not differentiate between different postal code regions on the basis of δ 15 N values in apples.…”
Section: Applesmentioning
confidence: 54%
“…Geological background, altitude [15], climate [16] and precipitation [17,18] cause a natural geographic variance in isotope ratios, but these are consistent within a given area. While stable water isotopes ( 2 H and 18 O) are suitable for differentiating large-scale regions [19,20], 13 C, 15 N and 34 S isotopes provide details of product origins on smaller scale [9,[21][22][23][24][25][26]. Plant water isotope composition (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, other factors, such as variety or site of production, could be more significant parameters influencing δ 13 C values in the section on botanical origin 34 . Another study performed on the whole apple fruits and three sub‐fractions (peel, pulp and seed) showed that δ 13 C and δ 15 N values were also able to discriminate apple varieties, but only when small geographical areas were considered 35 …”
Section: Resultsmentioning
confidence: 99%